Identification of nonclassical properties of light with multiplexing layouts - Sperling, Jan; Eckstein, A.; Clements, W. R.; Moore, M.; Renema, J. J.; Kolthammer, W. S.; Nam, S. W.; Lita, A.; Gerrits, T.; Walmsley, I. A.; Agarwal, G. S.; Vogel, W. (Physical Review A)

Entanglement in macroscopic systems - Sperling, Jan; Walmsley, I. A. (Physical Review A)

Quantum correlations in composite systems - Sperling, Jan; Agudelo, E; Walmsley, I A; Vogel, W (Journal of Physics B: Atomic, Molecular and Optical Physics)

Time-dependent quantum correlations in phase space - Krumm, F.; Vogel, W.; Sperling, Jan (Physical Review A)

Probing free-space quantum channels with laboratory-based experiments - Bohmann, M.; Kruse, R.; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review A)

Quantifying nonclassicality by characteristic functions - Ryl, S.; Sperling, Jan; Vogel, W. (Physical Review A)

Detector-Independent Verification of Quantum Light - Sperling, Jan; Clements, W. R.; Eckstein, A.; Moore, M.; Renema, J. J.; Kolthammer, W. S.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; Walmsley, I. A. (Physical Review Letters)

Direct calibration of click-counting detectors - Bohmann, M.; Kruse, R.; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review A)

Higher-order nonclassical effects in fluctuating-loss channels - Bohmann, M.; Sperling, Jan; Semenov, A. A.; Vogel, W. (Physical Review A)

Does price framing affect the consumer price sensitivity of health plan choice? - Schmitz, Hendrik; Ziebarth, N. R. (Journal of Human Resources, 52(1), 88-127)

Kollektivität und Lehrerkooperation – Zu Möglichkeiten der Konzeptualisierung und Erfassung von Professionalisierung durch Lehrerkooperationsprozesse - Bloh, Thiemo (Profession und Disziplin)

Challenges for Annotation Concepts in Music - Hadjakos, Aristotelis; Iffland, Joachim; Keil, Reinhard; Oberhoff, Andreas; Veit, Joachim (International Journal of Humanities and Arts Computing)

Learning {\ "o} natural infrastructures: A technology-centered approach to the development of new educational potentials - Keil, Reinhard (Education in the digital age - balance sheet and perspectives)

Gaussian Boson Sampling - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Barkhofen, Sonja; Silberhorn, Christine; Jex, Igor (Physical Review Letters)

Measuring topological invariants in disordered discrete-time quantum walks - Barkhofen, Sonja; Nitsche, Thomas; Elster, Fabian; Lorz, Lennart; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review A)

Webbasierte Classroom Response Systeme in der Hochschullehre - Eine designbasierte Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Herrmann, Philipp; Kundisch, Dennis; Magenheim, Johannes; Neugebauer, J. (Das Hochschulwesen)

On the efficient execution of bounded Jaro-Winkler distances - Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

A survey of current Link Discovery frameworks - Nentwig, Markus; Hartung, Michael; Ngonga Ngomo, Axel-Cyrille; Rahm, Erhard (Semantic Web)

Special issue on question answering for Linked Data - Ngonga Ngomo, Axel-Cyrille; Unger, Christina (Semantic Web)

Survey on challenges of Question Answering in the Semantic Web - Höffner, Konrad; Walter, Sebastian; Marx, Edgard; Usbeck, Ricardo; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

Radon - Rapid Discovery of Topological Relations - Ahmed Sherif, Mohamed; Dreßler, Kevin; Smeros, Panayiotis; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Thirty-First AAAI Conference on Artificial Intelligence, February 4-9, 2017, San Francisco, California, USA)

Holistic and scalable ranking of RDF data - Ngonga Ngomo, Axel-Cyrille; Hoffmann, Michael; Usbeck, Ricardo; Jha, Kunal (2017 IEEE International Conference on Big Data, BigData 2017, Boston, MA, USA, December 11-14, 2017)

Implementing scalable structured machine learning for big data in the SAKE project - Bin, Simon; Westphal, Patrick; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (2017 IEEE International Conference on Big Data, BigData 2017, Boston, MA, USA, December 11-14, 2017)

MOCHA2017: The Mighty Storage Challenge at ESWC 2017 - Georgala, Kleanthi; Spasic, Mirko; Jovanovik, Milos; Petzka, Henning; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Semantic Web Challenges - 4th SemWebEval Challenge at ESWC 2017, Portoroz, Slovenia, May 28 - June 1, 2017, Revised Selected Papers)

Open Knowledge Extraction Challenge 2017 - Speck, René; Röder, Michael; Oramas, Sergio; Espinosa Anke, Luis; Ngonga Ngomo, Axel-Cyrille (Semantic Web Challenges - 4th SemWebEval Challenge at ESWC 2017, Portoroz, Slovenia, May 28 - June 1, 2017, Revised Selected Papers)

7th Open Challenge on Question Answering over Linked Data (QALD-7) - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Haarmann, Bastian; Krithara, Anastasia; Röder, Michael; Napolitano, Giulio (Semantic Web Challenges - 4th SemWebEval Challenge at ESWC 2017, Portoroz, Slovenia, May 28 - June 1, 2017, Revised Selected Papers)

Wombat - A Generalization Approach for Automatic Link Discovery - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (The Semantic Web - 14th International Conference, ESWC 2017, Portorož, Slovenia, May 28 - June 1, 2017, Proceedings, Part I)

Eaglet - a Named Entity Recognition and Entity Linking Gold Standard Checking Tool - Jha, Kunal; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2017 Satellite Events - ESWC 2017 Satellite Events, Portorož, Slovenia, May 28 - June 1, 2017, Revised Selected Papers)

All that Glitters Is Not Gold - Rule-Based Curation of Reference Datasets for Named Entity Recognition and Entity Linking - Jha, Kunal; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - 14th International Conference, ESWC 2017, Portorož, Slovenia, May 28 - June 1, 2017, Proceedings, Part I)

The BigDataEurope Platform - Supporting the Variety Dimension of Big Data - Auer, Sören; Scerri, Simon; Versteden, Aad; Pauwels, Erika; Charalambidis, Angelos; Konstantopoulos, Stasinos; Lehmann, Jens; Jabeen, Hajira; Ermilov, Ivan; Sejdiu, Gezim; Ikonomopoulos, Andreas; Andronopoulos, Spyros; et al. (Web Engineering - 17th International Conference, ICWE 2017, Rome, Italy, June 5-8, 2017, Proceedings)

Characterizing mention mismatching problems for improving recognition results - Carlos Oliveira de Abreu, Jean; Fileto, Renato; Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Wittwer, Matthias; Saggion, Horacio (Proceedings of the 19th International Conference on Information Integration and Web-based Applications {&} Services, iiWAS 2017, Salzburg, Austria, December 4-6, 2017)

MAG: A Multilingual, Knowledge-base Agnostic and Deterministic Entity Linking Approach - Moussallem, Diego; Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference, K-CAP 2017, Austin, TX, USA, December 4-6, 2017)

Ensemble Learning of Named Entity Recognition Algorithms using Multilayer Perceptron for the Multilingual Web of Data - Speck, René; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference, K-CAP 2017, Austin, TX, USA, December 4-6, 2017)

SQCFramework: SPARQL Query Containment Benchmark Generation Framework - Saleem, Muhammad; Stadler, Claus; Mehmood, Qaiser; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference, K-CAP 2017, Austin, TX, USA, December 4-6, 2017)

Managing Lifecycle of Big Data Applications - Ermilov, Ivan; Ngonga Ngomo, Axel-Cyrille; Versteden, Aad; Jabeen, Hajira; Sejdiu, Gezim; Argyriou, Giorgos; Selmi, Luigi; Jakobitsch, Jürgen; Lehmann, Jens (Knowledge Engineering and Semantic Web - 8th International Conference, KESW 2017, Szczecin, Poland, November 8-10, 2017, Proceedings)

Torpedo: Improving the State-of-the-Art RDF Dataset Slicing - Marx, Edgard; Shekarpour, Saeedeh; Soru, Tommaso; M. P. Brasoveanu, Adrian; Saleem, Muhammad; Baron, Ciro; Weichselbraun, Albert; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Auer, Sören (11th IEEE International Conference on Semantic Computing, ICSC 2017, San Diego, CA, USA, January 30 - February 1, 2017)

Question Answering Over Linked Data: What is Difficult to Answer? What Affects the F scores? - Saleem, Muhammad; Nazari Dastjerdi, Samaneh; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Joint Proceedings of {BLINK2017:} 2nd International Workshop on Benchmarking Linked Data and NLIWoD3: Natural Language Interfaces for the Web of Data co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 21st - to - 22nd, 2017)

Benchmarking RDF Storage Solutions with IGUANA - Conrads, Felix; Lehmann, Jens; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2017 Posters {&} Demonstrations and Industry Tracks co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 23rd - to - 25th, 2017)

The Tale of Sansa Spark - Ermilov, Ivan; Lehmann, Jens; Sejdiu, Gezim; Bühmann, Lorenz; Westphal, Patrick; Stadler, Claus; Bin, Simon; Chakraborty, Nilesh; Petzka, Henning; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille; Jabeen, Hajira (Proceedings of the ISWC 2017 Posters {&} Demonstrations and Industry Tracks co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 23rd - to - 25th, 2017)

OKBQA: an Open Collaboration Framework for Development of Natural Language Question-Answering over Knowledge Bases - Kim, Jin-Dong; Unger, Christina; Ngonga Ngomo, Axel-Cyrille; Freitas, André; Hahm, YoungGyun; Kim, Jiseong; Choi, Gyu-Hyun; Kim, Jeonguk; Usbeck, Ricardo; Kang, Myoung-Gu; Choi, Key-Sun (Proceedings of the ISWC 2017 Posters {&} Demonstrations and Industry Tracks co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 23rd - to - 25th, 2017)

Federated SPARQL Query Processing Via CostFed - Potocki, Alexander; Saleem, Muhammad; Soru, Tommaso; Hartig, Olaf; Voigt, Martin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2017 Posters {&} Demonstrations and Industry Tracks co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 23rd - to - 25th, 2017)

Benchmarking Link Discovery Systems for Geo-Spatial Data - Saveta, Tzanina; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Joint Proceedings of {BLINK2017:} 2nd International Workshop on Benchmarking Linked Data and NLIWoD3: Natural Language Interfaces for the Web of Data co-located with 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 21st - to - 22nd, 2017)

A high-performance approach to string similarity using most frequent K characters - Valdestilhas, Andre; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 12th International Workshop on Ontology Matching co-located with the 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 21, 2017)

Iguana: A Generic Framework for Benchmarking the Read-Write Performance of Triple Stores - Conrads, Felix; Lehmann, Jens; Saleem, Muhammad; Morsey, Mohamed; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2017 - 16th International Semantic Web Conference, Vienna, Austria, October 21-25, 2017, Proceedings, Part II)

Distributed Semantic Analytics Using the SANSA Stack - Lehmann, Jens; Sejdiu, Gezim; Bühmann, Lorenz; Westphal, Patrick; Stadler, Claus; Ermilov, Ivan; Bin, Simon; Chakraborty, Nilesh; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille; Jabeen, Hajira (The Semantic Web - ISWC 2017 - 16th International Semantic Web Conference, Vienna, Austria, October 21-25, 2017, Proceedings, Part II)

Radon results for OAEI 2017 - Dreßler, Kevin; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 12th International Workshop on Ontology Matching co-located with the 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 21, 2017)

HOBBIT link discovery benchmarks at ontology matching 2017 - Röder, Michael; Saveta, Tzanina; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 12th International Workshop on Ontology Matching co-located with the 16th International Semantic Web Conference {(ISWC} 2017), Vienna, Austria, October 21, 2017)

SIGIR 2017 Workshop on Open Knowledge Base and Question Answering (OKBQA2017) - Choi, Key-Sun; Mitamura, Teruko; Vossen, Piek; Kim, Jin-Dong; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 40th International ACM SIGIR Conference on Research and Development in Information Retrieval, Shinjuku, Tokyo, Japan, August 7-11, 2017)

An evaluation of models for runtime approximation in link discovery - Georgala, Kleanthi; Hoffmann, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the International Conference on Web Intelligence, Leipzig, Germany, August 23-26, 2017)

CEDAL: time-efficient detection of erroneous links in large-scale link repositories - Valdestilhas, André; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille (Proceedings of the International Conference on Web Intelligence, Leipzig, Germany, August 23-26, 2017)

GENESIS: a generic RDF data access interface - Ermilov, Timofey; Moussallem, Diego; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Proceedings of the International Conference on Web Intelligence, Leipzig, Germany, August 23-26, 2017)

LOG4MEX: a library to export machine learning experiments - Esteves, Diego; Moussallem, Diego; Soru, Tommaso; Baron Neto, Ciro; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Cesar Duarte, Julio (Proceedings of the International Conference on Web Intelligence, Leipzig, Germany, August 23-26, 2017)

When in Doubt Follow the Crowd: How Idea Quality Moderates the Effect of an Anchor on Idea Evaluation - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 38th International Conference on Information Systems (ICIS))

Joint Proceedings of the 2nd RDF Stream Processing (RSP 2017) and the Querying the Web of Data (QuWeDa 2017) Workshops co-located with 14th ESWC 2017 (ESWC 2017), Portoroz, Slovenia, May 28th - to - 29th, 2017

Joint Proceedings of BLINK2017: 2nd International Workshop on Benchmarking Linked Data and NLIWoD3: Natural Language Interfaces for the Web of Data co-located with 16th International Semantic Web Conference (ISWC 2017), Vienna, Austria, October 21st - to - 22nd, 2017

Proceedings of the International Conference on Web Intelligence, Leipzig, Germany, August 23-26, 2017

ROCKER: A Refinement Operator for Key Discovery - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (CoRR)

MAG: A Multilingual, Knowledge-based Agnostic and Deterministic Entity Linking Approach - Moussallem, Diego; Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (CoRR)

Using Multi-Label Classification for Improved Question Answering - Usbeck, Ricardo; Hoffmann, Michael; Röder, Michael; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (CoRR)

Automatic Generation of Benchmarks for Entity Recognition and Linking - Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Moussallem, Diego; Usbeck, Ricardo; Speck, René (CoRR)

Mandolin: A Knowledge Discovery Framework for the Web of Data - Soru, Tommaso; Esteves, Diego; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (CoRR)

Machine Translation Using Semantic Web Technologies: A Survey - Moussallem, Diego; Wauer, Matthias; Ngonga Ngomo, Axel-Cyrille (CoRR)

"What is it Good for - Absolutely Nothing?" Exploring the Influence of Task Meaning on Creativity in Crowdsourcing - Görzen, Thomas (Proceedings of the 38th International Conference on Information Systems (ICIS))

Unter welchen Voraussetzungen kooperieren Grundschullehrkräfte im inklusiven Unterricht? Eine Studie zu den Bedingungen der Kooperationsbereitschaft von Grundschullehrerinnen und -lehrern im inklusiven Unterricht - Hellmich, Frank; Hoya, Fabian Karl; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
Als wichtige Bedingungen für die Realisierung inklusiven Unterrichts in der Grundschule gelten Kooperationen von Grund- und Sonderschullehrkräften. Bislang ist wenig darüber bekannt, unter welchen Voraussetzungen Grundschullehrkräfte Bereitschaft zur Kooperation im inklusiven Unterricht zeigen. Vor diesem Hintergrund haben wir 168 Grundschullehrkräfte einerseits zu ihrer Kooperationsbereitschaft im inklusiven Unterricht und andererseits zu ihren Einstellungen zur Inklusion und zur Teamarbeit, ihren Erfahrungen aus dem integrativen bzw. inklusiven Unterricht sowie ihren Selbstwirksamkeitsüberzeugungen für die Gestaltung des inklusiven Unterrichts befragt. Die Ergebnisse aus einem Strukturgleichungsmodell geben Hinweise auf die Bedeutungen der Einstellungen zur Teamarbeit und der Erfahrungen aus dem integrativen bzw. inklusiven Unterricht für die Kooperationsbereitschaft der Grundschullehrkräfte. (DIPF/Orig.)

Motivation für die Beschäftigung mit Inklusion während des Studiums bei Studierenden des Lehramts an Grundschulen - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Profession und Disziplin - Grundschulpädagogik im Diskurs)

Erfahrungen, Einstellungen und Motivation von Studierenden des Grundschullehramts in Hinblick auf den inklusiven Unterricht. - Görel, Gamze; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Self-efficacy of prospective Austrian and German primary school teachers regarding the implementation of inclusive education - Schwab, Susanne; Hellmich, Frank; Görel, Gamze (Journal of Research in Special Educational Needs)

Einstellungen von Kindern gegenüber Peers mit sonderpädagogischem Förderbedarf als Bedingungen der sozialen Partizipation im inklusiven Unterricht der Grundschule - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca (Inklusiver Unterricht in der Grundschule)

Primary school students’ implicit theories and their reading motivation. The role of parents’ and teachers’ effort feedback - Hellmich, Frank; Hoya, Fabian Karl (Zeitschrift für Psychologie)
Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The results of a structural equation model show that children’s perceptions of their parents’ effort feedback predict their implicit theories, their reading self-concepts, and their reading motivation. The correlation between children’s perceived parental effort feedback and their intrinsic reading motivation is mediated by their implicit theories. Children’s implicit theories and their reading motivation cannot be predicted by their perceptions of their teachers’ effort feedback.

Empirische Arbeit: Wahrgenommenes positives Feedback zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im Grundschulalter - Hellmich, Frank; Hoya, Fabian Karl (Psychologie in Erziehung und Unterricht)

Soziale Selbstkonzepte von Kindern im Grundschulalter und ihre Einstellungen gegenüber Peers mit Förderbedarf in der sozial-emotionalen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Inklusiver Unterricht in der Grundschule

Aktuelle Fragestellungen zu Produktion, Logistik und Controlling

Bitte stimmen Sie jetzt ab! - Ein Erfahrungsbericht über das Audience Response System PINGO - Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius (Proceedings der 15. e-Learning Fachtagung Informatik (DELFI 2017))

Study? Now! - Evaluation einer gamifizierten App zur Überwindung von akademischer Prokrastination - Klingsieck, K.; Bomm, A.; Djawadi, Behnud; Fahr, Rene; Feldotto, M.; John, Thomas; Kundisch, Dennis; Skopalik, A. (Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie (PAEPSY))

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century

Mahlzeitenmuster von Eltern in Paarbeziehungen - Klünder, Nina (Care und die Wissenschaft vom Haushalt)

Differenzierte Ermittlung des Gender Care Gap auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 - Klünder, Nina

Essalltag und Arbeitsteilung von Eltern in Paarbeziehungen – Eine quantitative Analyse auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02 - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
The article examines the division of labor for everyday food routines of two-parent households depending on their labor force participation. Using data from the representative German Time Use Survey 2001/02 and 2012/13, three different pairs were formed: dual-earner couples, couples with additional female income and male-breadwinner couples Findings show that mother’s employment influences the time used for everyday food routines: It was found that the higher the employment rate of mothers, the less time was spent on food routine activities. Furthermore, the daily time used for everyday food routines was reduced from 2001/02 to 2012/13. The largest reductions were seen in the group of mothers working fulltime. Besides that, fathers were more engaged in meal preparation on the weekends, although the responsibility was the mother’s. In addition, the age and number of children in a household influenced the time used for everyday food routines. However, none of the examined pair constellations can help determine an egalitarian division of everyday food routines. There is still a labor division by gender.
Zusammenfassung
Der Beitrag untersucht die zeitliche Gestaltung sowie die innerfamiliale Arbeitsteilung des Essalltags von Müttern und Vätern in Paarbeziehungen differenziert nach deren Erwerbsumfang. Die Sekundäranalyse erfolgt auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02, wobei drei Paarkonstellationen untersucht werden: Doppelverdiener-Paare, weibliche Zuverdiener- Paare sowie Paare mit männlichem Familienernährer. Die Analyse des Essalltags zeigt, dass der Erwerbsstatus der Mutter die zeitliche Gestaltung des Essalltags beeinflusst. Je höher dieser ist, desto weniger Zeit wird für die Ernährungsversorgung aufgewendet. Darüber hinaus hat sich die tägliche Zeitverwendung für die Ernährungsversorgung von 2001/02 bis 2012/13 reduziert, wobei die stärksten Einsparungen bei vollzeiterwerbstätigen Müttern zu konstatieren sind. Väter engagieren sich verstärkt am Wochenende bei der Mahlzeitenzubereitung, gleichwohl liegt die Verantwortung insgesamt bei den Müttern. Ebenso beeinflussen Alter und Anzahl der Kinder die Zeitverwendung für die Ernährungsversorgung. Letztlich kann in keiner untersuchten Paarkonstellation eine egalitäre Arbeitsteilung zur Gestaltung des Essalltags festgestellt werden. Vielmehr dominieren relativ ausgeprägte geschlechtsspezifische Arrangements.

Ausgewählte Ergebnisse der Zeitbudgeterhebungen 1991/92, 2001/02 und 2012/13 - Meier-Gräwe, Uta; Klünder, Nina (Familien stärken, Vielfalt ermöglichen. Bericht der familienpolitischen Kommission der Heinrich-Böll-Stiftung)

Generation Y. Wohin mit der Zeit? Ein empirischer Vergleich zur Zeitverwendung verschiedener Generationen - Zimmermann, Josepha; Klünder, Nina (Hauswirtschaft und Wissenschaft)

Towards a Lean Approach to Gamifying Education - John, Thomas; Feldotto, M.; Hemsen, P.; Klingsieck, K.; Langendorf, Mike (Proceedings of the 24th European Conference on Information Systems (ECIS))

Carbohydrates from Sources with a Higher Glycemic Index during Adolescence: Is Evening Rather than Morning Intake Relevant for Risk Markers of Type 2 Diabetes in Young Adulthood? - Diederichs, Tanja; Herder, C; Roßbach, S; Roden, M; Wudy, SA; Nöthlings, U; Alexy, U; Buyken, Anette (Nutrients)

Achieving More by Paying Less? How Retailers can Benefit by Bidding Less Aggressively in Paid Search Auctions - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Making Gamification Easy for the Professor: Decoupling Game and Content with the StudyNow Mobile App - Feldotto, M.; John, Thomas; Kundisch, Dennis; Hemsen, P.; Klingsieck, K.; Skopalik, A. (Proceedings of the 12th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Decomposing the Variance of Online Consumer Ratings and the Impact on Price and Demand - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop Theory in Economics of Information Systems (TEIS))

Using Information Cues to Identify High Quality Ideas in Crowd Evaluation - Görzen, Thomas; Kundisch, Dennis (2nd Workshop on IS Design and Economic Behavior (ISDEB))

Recommendation and Configuration of Value-Added Services for Repurposing Electric Vehicle Batteries: A Vertical Software Prototype - Klör, Benjamin; Monhof, Markus; Bräuer, Sebastian; Beverungen, Daniel (Proceedings of the 19th IEEE Conference on Business Informatics (CBI 2017))

Microservice-based Execution Environment for Service Compositions - Schürmann, Andreas
The microservice architecture uses independently running microservices as build- ing blocks for applications. These microservices are clearly bounded for each other and expose their functionality through, for instance, RESTful application inter- faces. Particularly the clear boundaries between microservices enable the reuse of microservice throughout different projects. Because of the increasing use of microservices, the composition of multiple microservices in service composition becomes a more important task. A challenging area in developing service compo- sitions is that it involves two distinct layers with few junctions. On the one hand, describes a service composition a business process, which involves multiple com- ponents. On the other hand, involves the implementation of a service composition topics like service discovery and message exchange protocols since the microser- vices involved in a service composition are located within a network environment. In this Bachelor’s Thesis, I describe a descriptions language to abstractly describe the business logic of a service composition. Furthermore, I describe a genera- tion process, which compiles this abstract description to a working microservice realizing the specified service composition. In addition to that, I provide an im- plementation of the generation process, as a proof of concept, and test it within a Kubernetes-based cluster environment.

The impact of customer reviews and advertisement efforts on the performance of experience goods in electronic markets - Frick, Bernd; Kaimann, Daniel (Applied Economics Letters)

The role of eWOM in the movie industry: The effect of online user ratings on box office sales - Zarindast, Mana

Optimizing the Structure of Nested Dichotomies: A Comparison of Two Heuristics - Melnikov, Vitalik; Hüllermeier, Eyke (Proceedings. 27. Workshop Computational Intelligence, Dortmund, 23. - 24. November 2017)

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, U.; Kalt, H.; Zrenner, Artur (JOURNAL OF LUMINESCENCE)
In this article we demonstrate a fully CMOS compatible fabrication process for the realization of microdisk resonators based on silicon oxynitride. The layer fabrication using plasma enhanced chemical vapor deposition is optimized in terms of surface roughness and internal material absorption. Resulting surface roughness due to the etching process is reduced by using optimized etching parameters. Whispering gallery modes of the fabricated microdisk resonators have been investigated by tapered fiber coupling and show quality factors as high as 10 6.

Polarization-entangled twin photons from two-photon quantum-dot emission - Heinze, Dirk; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum dots are promising sources for polarization-entangled photons. As an alternative to the usual cascaded biexciton-exciton emission, direct two-photon emission from the biexciton can be used. With a high-quality optical resonator tuned to half the biexciton energy, a large proportion of the photons can be steered into the two-photon emission channel. In this case the degree of polarization entanglement is inherently insensitive to the exciton fine-structure splitting. In the present work we analyze the biexciton emission with particular emphasis on the influence of coupling of the quantum-dot cavity system to its environment. Especially for a high-quality cavity, the coupling to the surrounding semiconductormaterial can open up additional phonon-assisted decay channels. Our analysis demonstrates that with the cavity tuned to half the biexciton energy, the potentially detrimental influence of the phonons on the polarization entanglement is strongly suppressed—high degrees of entanglement can still be achieved. We further discuss spectral properties and statistics of the emitted twin photons.

Interaktive, digitale Einkaufserlebnisse in Innenstädten - Hendrik Betzing, Jan; Beverungen, Daniel; Becker, Jörg; Matzner, Martin; Schmitz, Gertrud; Bartelheimer, Christian; Berendes, Carsten Ingo; Braun, Marina; Gadeib, Andera; Hoffen}, Moritz {von; Schallenberg, Christian (HMD Praxis der Wirtschaftsinformatik)

Ensembles of Context and Form for Repurposing Electric Vehicle Batteries: An Exploratory Study - Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Klör, Benjamin; Monhof, Markus (Computer Science --- Research and Development)

Information systems for smart services - Beverungen, Daniel; Matzner, Martin; Janiesch, Christian (Information Systems and E-Business Management)
Digital interactions among businesses and consumers through powerful information systems and omnipresent connected devices establish today’s networked society. In this light, Service Science continues to take root as a research discipline that focuses on the integration of (digital) resources by service providers and service customers for value co-creation in service systems. Rapid advances in information technology allow for designing novel information systems that enable entirely new configurations of service systems. In turn, Service Science also leaves its mark on the design, adoption, and use of information systems and technology. With this special issue, we compile a set of timely papers that investigate selected facets of the complex interplay between information technology, information systems, and Service Science to design innovative IT artifacts for smart service. This editorial opens this special issue by elaborating on our understanding of smart service.<br
Keywords: Information system; Smart service; Service system

Testing Java Method Contracts - Börding, Paul

Radar backscattering from a large-grain cometary coma: numerical simulation - Dogra, Shraddha; Grynko, Yevgen; Zubko, Evgenij; Förstner, Jens (Astronomy & Astrophysics)
We numerically simulate the circular polarization ratio of the radar signal backscattered from a large-grain cometary coma and compare the simulation results with the radar measurements for seven comets. We apply the discrete dipole approximation method and a model of random irregular particles. Our results confirm water ice composition of the cm-sized chunks detected by the NASA Deep Impact space probe in the vicinity of the nucleus of Comet 103P/Hartley 2. The index of the power-law size distribution in this case can be constrained to the range n ≈ 3.3–4.3. For the other considered comets the circular polarization ratio can be reproduced with variations of the power index between 2 and 5.
Keywords: tet_topic_scattering

How to Handle Dilemmas in Triadic Service Relationships – An Exploratory Study. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)